PL201, a Reported Rhamnoside Against Alzheimer's Disease Pathology, Alleviates Neuroinflammation and Stimulates Nrf2 Signaling - An, Yuqian; Zhang, Hong; Huang, Shichao; Pei, Gang (Frontiers in Immunology, 2020)
Neuroinflammation induced by over-activated glia cells is believed to be a major hallmark of Alzheimer’s disease (AD) and a hopeful target against AD. A rhamnoside PL201 was previously reported to promote neurogenesis and ameliorate AD pathologies, and in this study we revealed that PL201 also significantly reduced accumulation of the activated microglia and pro-inflammatory cytokines in APP/PS1 mice. In vitro, PL201 consistently suppressed the microglia induction of pro-inflammatory cytokines after stimulation with lipopolysaccharides and Aβ42. Further mechanistic studies demonstrated that PL201 considerably enhanced the expression level and the nuclear translocation of Nrf2, a key regulator of neuroinflammation. Moreover, PL201 effectively stimulated Nrf2 signaling cascade, including up-regulation of HO-1 and down-regulation of NF-κB pathway. Thus, our findings indicated the anti-neuroinflammatory effect by PL201 in vivo and suggested PL201 or the alike with multiple functions such as neurogenesis, mitochondria maintenance, and anti-neuroinflammation, could be a promising candidate in AD treatment.